Pengaruh Komunikasi Internal Terhadap Produktivitas Kerja Pegawai Kantor Kecamatan Taniwel Timur - Ririanty Ririanty; Elsina Huberta Aponno; Jean Rosalina Asthenu; Cynthia Imelda Tjokro (P3M Politeknik Negeri Ambon, 2026)
ABSTRACT This study aims to determine the influence of internal communication on work productivity at the Taniwel Timur District Office. The background of this research lies in the fact that internal communication within the office has not been running effectively. This research employs a quantitative approach. Data were collected using a survey method by distributing questionnaires to 30 employees of the Taniwel Timur District Office. The analytical method applied was simple linear regression analysis with the assistance of SPSS 27.0 software. The results of this study indicate that the hypothesis is accepted, showing a positive and significant effect with a probability value of 0.000 (p < 0.05). These findings confirm that the better the internal communication, the higher the employee work productivity will be. Conversely, poor internal communication tends to decrease employee work productivity. Keywords: Internal Communication, Work Productivity